Epidemic process of tularemia in the world and in the south of Ukraine - Jurtubaeva, G.; Savchuk, A.; Kozishkurt, O.; Gerasimenko, O.; Gaidei, V.; Kostolonova, L. (Journal of Education, Health and Sport, 2022)
Present day tularemia prevalence in the world and in Ukraine is described as well as the current epidemic and epizootic situation in various regions. The mechanisms of transmission of the pathogen are discussed. The causative agent of tularemia Francisella subsp. tularensis is one of the most virulent microorganisms of the highest priority (category "A"). This can be used as a biological weapon, and so poses a real threat to the humanity’s security. Human infection occurs as a result of bites by infected blood-sucking arthropods (mosquitoes, thrips, ticks), consumption of rodent-contaminated food and water, inhalation of air-dust aerosol from diseased rodents contaminated with the pathogen, and also after direct contact with infected animals (hunting, caring for pets, carcass processing). Isolates of the most virulent for humans and animals subspecies F. tularensis subsp. tularensis circulate only in North America. The less virulent subspecies F. tularensis subsp. Holarctica circulates in North America, Europe, Asia (Japan), Australia (including Tasmania). The wide distribution of this subspecies in the world is due to its ability to exist in the aquatic environment. In most European countries, the terrestrial cycle of existence of the tularemia microbe is dominant, in the body of small mammals and carriers of the pathogen - mosquitoes, ticks, and whiteflies. The main clinical form of tularemia is ulcerative-bubonic, it is quite easily diagnosed, infection occurs as a result of bites by infected blood-sucking arthropods. Anginal-bubonic and gastrointestinal forms are diagnosed in hot countries, they are associated with the consumption of food and water contaminated by rodents. In the nearest future the worsening of tularemia epidemic situation in various regions of the world is predicted due to the activation of enzootic centers and lack of vaccination of risk groups persons and the population of endemic areas.